KONSEP DISKRESI KEPOLISIAN DALAM PROSES PIDANA - Ansori Ansori (Perspektif, 2005)
Diskresi represent the kewenangan free from the Police Republic of indonesia to determine the stages; steps in course of crime. Diskresi Police executed by pursuant to Law No 2 Th. 2002 about State police of Republic of Indonesia also conducted by construction of profession and code of etik profession of to be action of State police functionary accountable Republic of Indonesia judicially and also moral.